"Those who died are the ones that are cured". Walking the political tightrope of Nodding Syndrome in northern Uganda: Emerging challenges for research and policy - Irani, Julia; Rujumba, Joseph; Mwaka, Amos Deogratius; Arach, Jesca; Lanyuru, Denis; Idro, Richard; Gerrets, Rene; Grietens, Koen Peeters; O’Neill, Sarah (PLOS Neglected Tropical Diseases, 2019)
Author summary Nodding Syndrome, a form of epilepsy that occurs in onchocerciasis-endemic areas has affected about 3000 children in Northern Uganda where the epidemic emerged at the time of the civil war. Although an association with onchocerciasis has been established, the disease etiology has not yet been identified. In conjunction with the area’s history of war, political conflict and ethnic divides, many affected people were suspicious of government health interventions and scientific studies. Furthermore, ambiguities around the disease etiology leaves room for several interpretations, which in addition to distrust leads to rumours, that may hinder future interventions. In view of improving adherence to health interventions, this article explains the socio-political nature of Nodding Syndrome in Northern Uganda. We show how and why this disease has been politicised in Uganda; how this politicisation has affected research and dissemination; and, the implications this has for disease control. The insights presented will be critical for reducing resistance to research, to treatment and to the dissemination of knowledge which is necessary for the prevention and control of Nodding Syndrome and onchocerciasis in Northern Uganda.